The Relationship between Self-Effiacy and video Learning on the Students Listeny Comprehension Level A1 - Kristin Simanjuntak; May Demanty; Ruth Krenia Barus; Thesa Febrianti Sihombing (CV. Rayyan Dwi Bharata, 2026)
This study aims to examine the relationship between students’ self-efficacy and the use of video-based learning in improving listening comprehension at the A1 level. Listening comprehension is considered one of the essential skills in learning a foreign language, particularly for beginner learners. Nevertheless, many students face challenges in understanding spoken language because of limited vocabulary and a lack of confidence. Self-efficacy, which refers to students’ beliefs in their capability to successfully perform learning tasks, is an important factor that can influence their learning performance. In addition, video-based learning has increasingly been used as an effective instructional medium since it combines both visual and auditory elements that support the learning process. This study employed a quantitative correlational research design. The participants consisted of university students at the A1 level in the German Language Education program. The data were gathered using a self-efficacy questionnaire and a listening comprehension test. The findings revealed a positive correlation between students’ self-efficacy and their listening comprehension achievement. Moreover, the implementation of video-based learning was found to support better listening performance among students. These results indicate that strengthening students’ self-efficacy and integrating video-based learning into the teaching process can contribute to the improvement of listening comprehension at the beginner level.